Debt maturity structure in private firms: Does the family control matter? - Díaz-Díaz, Nieves Lidia; García-Teruel, Pedro J.; Martínez-Solano, Pedro (Journal of Corporate Finance, 2016)
This research studies the effect of family control on the debt maturity structure of private firms. It uses a sample of unlisted Spanish firms for the period 2004–2013. Our results indicate that family firms get better access to long-term debt, even when exercising control by pyramid structures. However, the presence of a second largest family shareholder has a negative effect on debt maturity. Moreover, in line with previous studies, we find that firms use more long-term debt when they have fewer growth opportunities, higher asset maturity and are more leveraged.